CONSTIPATION AS A CAUSE OF ANAL FISSURE, MYTH OR TRUTH - Khan, Khalid; Mufti, Tariq; Rehman, Zia -ur-; Griffon, Samson (Journal of Ayub Medical College Abbottabad, 1999)
A study was done to find correlation between constipation and Anal Fissure. Performa were distributed among 100 people asking them history of constipation and Anal Fissure. In our study 14 people had Anal Fissure with 11 out of them having constipation which strongly supports the hypothesis that constipation is cause or precipitating factor for Anal Fissure.